Abbreviated MRI and Accelerated MRI for Screening and Diagnosis of Breast Cancer. Issue 5 (October 2017) - Sheth, Deepa; Abe, Hiroyuki
Abstract : Abstract: Although published studies have revealed that magnetic resonance imaging (MRI) is by far the most effective imaging modality for cancer detection, it is currently considered cost-ineffective for screening women at an intermediate risk for breast cancer. The concept of an "abbreviated MRI" protocol has recently emerged as a possible solution for reducing the cost of MRI. The abbreviated MRI is a shortened version of the standard MRI, consisting of a single early phase dynamic contrast enhanced (DCE) series. Several clinical studies have shown that this MRI protocol would not affect sensitivity or specificity for breast MRI screening purposes. In clinical practice, morphologic evaluation and kinetic assessment are 2 major components of the interpretation process. However, kinetic assessment cannot be performed with the abbreviated protocol, because multiple sets of post-contrast images are necessary for the generation of kinetic curves. "Accelerated MRI" is a collective term for imaging techniques that acquire DCE-MR images in a very short time. Published studies suggest that the kinetic assessment during the very early post-contrast phase obtained with the accelerated MRI techniques is comparable to that with the standard MRI techniques. Applying accelerated MR techniques could potentially enhance the abbreviated MRI protocol in terms of diagnostic potential, while maintaining the shorter study time. Thus, the abbreviated MRI protocol associated with accelerated MRI techniques may provide value for screening and for diagnostic purposes.